2009
DOI: 10.1007/s00339-008-5039-4
|View full text |Cite
|
Sign up to set email alerts
|

Key role of molecular kinetic energy in early stages of pentacene island growth

Abstract: Organic molecular beam deposition is studied systematically at thermal and hyperthermal regimes aiming at investigating the role of molecular kinetic energy on the growth mechanism of pentacene submonolayers on SiO x /Si. We show that the kinetic energy of the impinging molecule (E k ) plays a crucial role in determining island structure and shape, distribution of island sizes, the crystalline quality of the first monolayer, and even the growth mode of subsequent layers. With increasing E k , the island struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…The molecular islands formed in each layer mimic exactly the geometrical shape of the larger islands underneath. [31] Pentacene islands in Figure 1a signify the typical crystal facets with regular geometric shape with very sharp and straight island edges. This implies a homoepitaxial-like growth among the intra-pentacene layers.…”
Section: Single-layer Pentacene Field-effect Transistors Using Electrmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular islands formed in each layer mimic exactly the geometrical shape of the larger islands underneath. [31] Pentacene islands in Figure 1a signify the typical crystal facets with regular geometric shape with very sharp and straight island edges. This implies a homoepitaxial-like growth among the intra-pentacene layers.…”
Section: Single-layer Pentacene Field-effect Transistors Using Electrmentioning
confidence: 99%
“…High crystallinity in the pentacene was achieved by carrying out the SuMBD at a kinetic energy of 6.4 eV. [31] Reference morphology analysis were performed by examination of monolayers deposited on bare silicon oxide using ex situ tapping mode atomic force microscopy (AFM) and X-ray diffraction (XRD). Prior to the deposition of pentacene on the FET substrates, the lithographically patterned gold source and drain electrodes on a standard heavily doped Si substrate with a 250 nm SiO 2 gate insulator, were covered with SAMs of thiols with opposing dipole moments.…”
Section: Single-layer Pentacene Field-effect Transistors Using Electrmentioning
confidence: 99%
“…Wu et al have achieved five layers in the desired LbL growth for the important case of 5A on SiO x by using SuMBD [149]. Using conventional OMBD, Zhang et al showed the strain relaxation driven transition from LbL to rapid roughening after 5 layers for the plate-like molecule DIP [150].…”
Section: Layer-by-layer Growth Of Lying Moleculesmentioning
confidence: 99%
“…14,28 Under our experimental conditions, the kinetic energy of 6.4 eV was achieved by properly varying the degree of seeding through changing the He carrier gas pressure.…”
mentioning
confidence: 99%
“…24 The kinetic energy of the impinging molecules can thus be tuned from less than 1 eV up to several tens of eV, i.e., within a range of energies of surface processes such as elastic-inelastic scattering, physisorption, chemisorption, and activation of surface chemical reactions. Hyperthermal energies reached using supersonic beam methods have given access to controlling growth, 25 reactivity, 26 morphology and structure 27,28 of molecular thin films beyond the level achievable by OMBD.…”
mentioning
confidence: 99%